Clinical and epidemiological profile of tuberculosis patients diagnosed in a university hospital (Brazilian Journal of Health Research, 2020)
Introduction: Tuberculosis is an infectious disease that represents a serious public health issue, since it affects approximately one third of the world’s population. Objective: Analyzing the clinical and epidemiological profile of patients diagnosed with tuberculosis in a university hospital. Methods: Cross-sectional, retrospective, quantitative study comprising 118 patients diagnosed with tuberculosis from January 2013 to December 2017. Data collection was based on a form encompassing sociodemographic and epidemiological variables, which was elaborated based on the investigation form used by the Information System for Notifiable Diseases. Data were analyzed in SPSS® software. The research was approved by the Research Ethics Committee of the University Hospital of Federal University of Piauí. Results: There was prevalence of tuberculosis among male patients who had low schooling, brown skin color and who came from other counties in Piauí State. Based on the bivariate analysis, elderly patients with positive sputum smear microscopy, suspected x-ray, positive culture and detectable rapid molecular test were more prone to be diagnosed with the pulmonary form of the disease. Conclusion: There was high percentage of patients with pulmonary tuberculosis diagnosed in the hospital service, although both the diagnosis and treatment are available in the primary care. In addition, it was evident that social determinants play a key role in the incidence of tuberculosis cases among lower-income populations.
Keywords: Tuberculosis; Epidemiology; Public Health; Diagnostics